PENDAMPINGAN SISWA TERHAMBAT MENGHITUNG DENGAN MEDIA SEMPOA BIJI KARET DI SD NEGERI 03 SEMULI RAYA - Fhela Vhantoria Ningrum (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2023)
Assistance for students who are hampered from counting using rubber seed abacus media at SD Negeri 03 Semuli Raya is one of the KKN activity schemes for FKIP UMKO students. The results of initial observations identified that out of 10 students, only 2 students were fluent in arithmetic. The purpose of this activity is to improve students' numeracy skills at SD Negeri 03 Semuli Raya and assist students in learning to count using a rubber seed abacus. Participants who took part in this activity were grade 2 students with a total of 10 students. Based on the results of the evaluation of this activity, 80% of students received a score excelent. In addition, the enthusiasm of the students was very high in the process of mentoring arithmetic using a rubber seed abacus as evidenced by the presence of the participants during the 5 meetings they were always present. Another finding is that only rubber seeds can be found easily and for free but can be used as learning media in the form of an interesting abacus for students learning to count.